Financial and economic mechanism as a universal instrument for transfer of land use to the model of sustainable development - Dorosh, O.; Fomenko, V.; Kupriyanchik, I.; Svyrydova, L. (Land Management, Cadastre and Land Monitoring, 2019)
It has been found that pursuing a state policy in the field of land relations in order to obtain economic benefits without taking into account environmental interests has caused an ecological crisis in land use, as evidenced by the results of the classification in the world environmental rating of Ukraine (102nd place among 132 countries). From these positions, 5 billion is lost in economic equivalents due to poor crop yields on contaminated and degraded lands, with indirect losses reaching up to one billion hryvnias (40 million). It is proved that the existing disparities can be adjusted by the use of universal tools for implementing the financial and economic mechanism of influence on economic entities in order to achieve environmentally safe land use, focusing on the factors that shape the possibilities of using a specific type of instruments, namely: economic incentives, economic guarantees, market, mortgage, fiscal and innovative. Keywords: financial and economic mechanism, instruments, sustainable land use